Potentiality of Kernel Density Estimation Tool for Tropical Cyclone Frequency Analysis in Bangladesh - Tuya, Jannatun Hussna; Coalee, Ummul Momanin; Ahmed, Raju (The Jahangirnagar Review, 2024)
Bangladesh is particularly vulnerable to cyclones and storm surges because of its unique geographical location and climatic variability. Bangladesh suffered numerous destructive cyclones that destroyed lives and property. The 1970 Bhola cyclone, 1991 Gorky cyclone, and 2007 Sidr cyclone caused many deaths, massive economic loss, and infrastructural destruction. In this context, cyclone risk zoning provides crucial insights and viewpoints that help communities, governments, and organizations plan for and reduce its consequences. Hence, using kernel density estimation to analyze cyclone risk zoning in Bangladesh may offer valuable comprehension. The researcher collected the required secondary data from BMD, IMD, EM-DAT, JTWC etc., to prepare a vast GIS database for cyclone hazards in Bangladesh. The spatial distribution of tropical cyclones in Bangladesh has been analyzed using ArcGIS tools like, track digitization, kernel density estimation etc. The kernel density estimation has been performed in 1960 to 2023 cyclone frequency and track data. A detailed mapping of cyclonic events across the Indian Ocean was followed by an analysis of tropical cyclone frequency in Bangladesh, taking into consideration their Bay of Bengal distribution. The geographical distribution of cyclonic activity shows that the northern Bay of Bengal is more prone to tropical cyclones than the southern bay. The kernel density calculation illustrates three prominent cyclone risk zones: high-risk, moderate-risk, and high-wind-risk. Kernel density analysis provides a detailed comprehension of regions characterized by a high concentration of cyclone impact. This strategy can help with resource allocation and focusing activities on areas that demand more concern.